1989
DOI: 10.1126/science.2787531
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to Interleukin-5 Inhibits Helminth-Induced Eosinophilia in Mice

Abstract: When rodents are infected with the nematode Nippostrongylus brasiliensis, large numbers of eosinophils appear in their blood and lungs and their serum immunoglobulin E (IgE) is increased. Injection of a monoclonal antibody to interleukin-5 completely suppressed the blood eosinophilia and the infiltration of eosinophils in the lungs of parasitized mice but had no effect on serum IgE. In contrast, an antibody to interleukin-4 inhibited parasite-induced IgE but not the eosinophilia. These results show that interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
302
0
3

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 586 publications
(329 citation statements)
references
References 20 publications
24
302
0
3
Order By: Relevance
“…A llergic immunopathology and host protection against helminth parasites are both mediated, in large part, by the type 2 cytokines IL-4, IL-5, IL-9, and IL-13 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Of these, a particularly prominent role is played by two related cytokines, IL-4 and IL-13.…”
mentioning
confidence: 99%
“…A llergic immunopathology and host protection against helminth parasites are both mediated, in large part, by the type 2 cytokines IL-4, IL-5, IL-9, and IL-13 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Of these, a particularly prominent role is played by two related cytokines, IL-4 and IL-13.…”
mentioning
confidence: 99%
“…Many investigators have demonstrated a direct correlation between eosinophilia and IL-5 in human helminth infection and in experimental animal models. It has also been demonstrated that anti-IL-5 mAb treatment inhibits eosinophilia in mice infected with Toxocara canis, Nippostrongylus brasiliensis and Schistosoma mansoni (14)(15)(16). In addition, IL-5 plays an important role in mobilizing eosinophils from bone marrow to peripheral blood and in priming eosinophils to respond easily to other chemotactic stimuli such as chemokines and lipid mediators (7,17).…”
mentioning
confidence: 99%
“…Other allergic pulmonary and non-pulmonary allergic diseases -There is a strong association between IL-5 and eosinophilia in a number of allergic human diseases, including parasitic infections (Coffman et al 1989, Limaye et al 1993, Hagan et al 1996, atopic dermatitis (Frew & Kay 1988, Hamid et al 1994, eosinopilic myocarditis (Desreumaux et al 1993), hypereosinopilic syndrome (Schrezenmeier et al 1993, Satoh et al 1994) eosinophilic gastroenteritis (Quan et al 1993, Dubucquoi et al 1995, allergic rhinitis , chronic eosinophilic pneumonia and other eosinophilic lung diseases (Walker et al 1994) (Fig. 1).…”
Section: Asthma and Il-5 Human Studies: Il5 Mrna And Proteinmentioning
confidence: 99%
“…However, only IL-5 was selective for the eosinophil lineage (Clutterbuck et al 1989). Transgenic mice which constituitively express IL-5 have high level, lifelong eosinophilia (Dent et al 1990) and the administration of anti-IL-5 neutralising antibody in parasite infected mice totally blocks the production of eosinophilia (Coffman et al 1989.…”
Section: Il-5 T Cells and Eosinophilsmentioning
confidence: 99%